Pengaruh Media Tanam dan Konsentrasi Pupuk Organik Cair (POC) Urin Sapi Terhadap Pertumbuhan Semai Kayu Putih - Melkianus Wawo; Wilhelmina Seran; Astin E. Mau (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
The eucalyptus plant (Melalauca leucadendron Linn.) is one of the largest essential oil producing plants in Indonesia. The main objective of developing eucalyptus plantations from an economic perspective is to extract the leaves. To support the development of eucalyptus plantations, of course there must be availability of plant cultivation, so there is a need for efforts to provide quality seeds. This research was conducted in the Fatukoa Permanent Nursery, Fatukoa Village, Kupang City which was carried out for 4 months, from April to July 2022. The method used in this study was a 2-factor Completely Randomized Design (CRD) with a combination of treatment with POC concentrations of cow urine and planting media. The results showed that the interaction between the planting medium and the POC concentration of cow urine had a significant effect on height but had no effect on stem diameter, number of leaves, dry weight and percentage alive. The single factor of growing media had an effect on height and diameter but had no effect on the number of leaves, dry weight and percentage of life. While the single factor POC concentration of cow urine has an influence on height, diameter, number of leaves, dry weight and percentage alive.